Detection of Aedes Aegypti larvae frequency range using signal processing method. (2019) - Fuad, M.A.M.; Jali, M.H.; Ghani, M.R.A.; Ghazali, R.; Sulaima, M.F.; Aziz, M.A.; Soon, C.C.
Abstract: Aedes Aegypti mosquitoes is a small slender fly insect that spread the arbovirus from flavivirus vector to human body during the feeding process. The early detection of this species is very important because once these species turn into adult mosquitoes the population control becomes more complicated. This paper presents a discovery on the frequency range detection of Aedes Aegypti larvae using signal processing method by comprehending its behaviour and biological structures. Based on the signal processing technique, the system will frame the larvae frequency when the hydrophone is used to detect the movement. This technique is attained by connecting a hydrophone to the pre-amplifier circuit that will improve the quality of the signals generated by the hydrophone before they are converted into a suitable signal. This experiment acquired the movement frequency for 100 larvae of 4 th instar Aedes Aegypti species. The 4 th moult or instar is selected during the test as it has a significant breathing tube and can be seen clearly in the water although in its rest circumstances. In the test, the water condition is another important property to be observed. The constraint is to distinguish the difference between with and without the presence of water droplet. The system is impulse the signal chart and the results are analysed by using spectrogram and periodogram from time-frequency domain analysis via MATLAB. It shows that the Aedes Aegypti larvae power spectral density range is between -10 dB/Hz to 20dB/Hz. From the experiment, it is concluded that the finding of this project can be implemented through the development of effective and efficient control system to combat the spreading of flavivirus vector.